2019
DOI: 10.1017/s1047951119000350
|View full text |Cite
|
Sign up to set email alerts
|

Adverse events within 1 year after surgical and percutaneous closure of atrial septal defects in preterm children

Abstract: Introduction:Atrial septal defect is the third most common CHD. A hemodynamically significant atrial septal defect causes volume overload of the right side of the heart. Preterm children may suffer from both pulmonary and cardiac comorbidities, including altered myocardial function. The aim of this study was to compare the rate of adverse events following atrial septal defect closure in preterm- and term-born children.Method:We performed a retrospective cohort study including children born in Sweden, who had a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 43 publications
1
3
0
Order By: Relevance
“…The incidence of postoperative complications in symptomatic patients in our study was low [19] and comparable with reports in older asymptomatic patients [18,21,22]. Tanghoj et al studied risk factors for adverse events following transcatheter and surgical ASD closure in children born preterm and concluded that prematurity was not a risk factor for post-procedural complications despite earlier procedural age, larger ASD size, and higher comorbidity than term infants [23,24].…”
Section: Hemodynamic Improvement Granted By Asd Closuresupporting
confidence: 85%
“…The incidence of postoperative complications in symptomatic patients in our study was low [19] and comparable with reports in older asymptomatic patients [18,21,22]. Tanghoj et al studied risk factors for adverse events following transcatheter and surgical ASD closure in children born preterm and concluded that prematurity was not a risk factor for post-procedural complications despite earlier procedural age, larger ASD size, and higher comorbidity than term infants [23,24].…”
Section: Hemodynamic Improvement Granted By Asd Closuresupporting
confidence: 85%
“…Adverse events were categorised according to severity and were presented in detail in a previous publication. 20 The risk factor "Symptomatic atrial septal defects" was used when stated in the medical journal as diagnoses related to heart failure according to International classification of disease (ICD 10 I50.0-9) and/or if the child was treated with antidiuretic drugs. 21,22 The risk factor "pulmonary hypertension" was used when echocardiographic findings indicated a systolic right ventricular pressure ≥25 mmHg, by measures of the tricuspid regurgitant velocity > 2.6 m/second, or when invasive catheter measurements showed a mean pulmonary artery pressure of ≥25 mmHg pulmonary or a pulmonary vascular resistance of ≥3 WU × m 2 , all prior to the atrial septal defect closure.…”
Section: Methodsmentioning
confidence: 99%
“…In our study, the risk of an early ASD closure was associated with estimated ASD size:bodyweight ratio of 0.8 and of 2.0, even after adjustments for potential confounders. In a previous study, we did not find an increased risk of adverse events following ASD closure for children with large or small ASD size:bodyweight ratios (13). This indicates that the ASD size:bodyweight ratio cannot be the only predictor of the need for an early closure nor for the risk of adverse events.…”
Section: Asd Size:bodyweight Ratiomentioning
confidence: 60%
“…The study included all children born in Sweden who were treated with an ASD closure, surgically or percutaneously, before the age of 18, between January 2000 and December 2014 at Skåne University Hospital in Lund and the Astrid Lindgren Children's Hospital at Karolinska University Hospital in Stockholm, Sweden. This cohort was studied in a previous study on adverse events after ASD closure (13). Cases were children aged 2 years or younger at the time of ASD closure.…”
Section: Methodsmentioning
confidence: 99%